Sistem Pendukung Keputusan Pemilihan Lokasi Franchise Menggunakan Metode Topsis Di Wilayah Kota Surakarta - Navin Ramadhan; Bagas Pramudya; Muhammad Hashfi Rafid Muttaqin (Prosiding Seminar Nasional Teknologi Informasi dan Bisnis, 2023)
To find the optimal location to place a franchise business, a decision support system (DSS) is needed that helps determine the best area to choose a franchise deployment location. One way to overcome the problem of selecting franchise distribution locations is to use the TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) method, which is a multi-criteria decision making method based on the principle that the chosen alternative must have the shortest distance to the positive ideal solution and the shortest distance to the ideal solution. longest with a negative ideal solution. The processes carried out in the TOPSIS method include calculating the normalization matrix, calculating the weighted normalization matrix, determining the positive ideal solution and negative ideal solution, calculating the distance between each alternative and the ideal solution, and calculating the preference value for each alternative. By utilizing the TOPSIS method, information is obtained regarding the selection of the franchise location closest to the preferences required by the company.